Directionality/Flow - Jędrzejko, Paweł (Review of International American Studies, 2017)
Paweł Jędrzejko Department of American and Canadian Studies Institute of English Cultures and Literatures University of Silesia in Katowice Poland Directionality/Flow Abstract: The present volume, generously guest-edited by Claudio Salmeri of the University of Silesia in Katowice, Poland, offers a multifaceted insight into how American values have been “translated into Italian” and accommodated within the cultural space of twenty-first century Italy. The volume’s title, Trans/Lazio, is thus both a gesture in recognition of the complexity of the Italian cultural space and an attempt to accommodate theoretical premises of polysystem theory in a study of the mutual relations between Italy and America as simultaneously donor and acceptor cultures, simultaneously distinctive and accommodating. Emphasizing these values, the present, aptly titled, issue ushers in the second decade of RIAS, a journal univocally dedicated to the hemispheric and transoceanic study of the Americas.